Penerapan Metode Klasifikasi Decision Tree dalam Prediksi Kanker Payudara Menggunakan Algoritma C4.5 - Nurjoko, Nurjoko; Hendra, Hendra Kurniawan; Cici Cahyati; Elvira Uthia Rustanti; Hiya Cahya Mujahidah; Amanda Putri Maharani; Rosita; Agus Rahardi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
Breast cancer is a deadly disease that require early detection and accurate prediction to improve recovery chance. This research aims to predict breast cancer using Data Mining technique with Decision Tree C4.5 algorithm. The dataset includes attributes such as tumor size, estrogen status, progesterone status, Progesterone Status, Survival Month, and status. These attributes were selected based on their clinical relevance and predictive potential in the context of breast cancer. The classification results showed a high level of accuracy with a prediction history of 658 surviving breast cancer patients and a precision class of 91.90%. This study has an accuracy rate of 89,81%. These findings have the potential to be developed int a medical decision support system to assist in more objective and efficient.   Keywords—Breast Cancer, Data Mining, Decision Tree, C4.5, Prediction, Accuracy